Roux-en-Y pancreaticojejunostomy reconstruction after deep enucleation of benign or borderline pancreatic lesions: a single-institution experience - Xiao, Zhiwen (HPB (Oxford), 2016)
BACKGROUND: Standard pancreatectomy for benign and borderline pancreatic lesions involves resecting a substantial amount of normal pancreatic parenchyma and leads to a subsequent impairment of both exocrine and endocrine pancreatic functions. A limited resection such as enucleation is the preferred option for such neoplasms. However, enucleation is associated with a high risk of postoperative complications in some cases. This study evaluated the feasibility and outcomes of performing deep enucleation with Roux-en-Y pancreaticojejunostomy reconstruction. METHODS: This study included patients who underwent pancreatic lesion enucleation from February 2010 to April 2014 in our hospital. The clinical data were collected and retrospectively analyzed. RESULTS: This study examined 53 patients who underwent enucleation, 33 of the procedures included deep enucleation with Roux-en-Y pancreaticojejunostomy reconstruction. There was no mortality, and the morbidity rate was 66.7% in this group. No patients developed grade C pancreatic fistulas in both group. None of the patients developed tumor recurrence or exocrine or endocrine insufficiency at a median follow-up of 25 months. DISCUSSION: Enucleation with Roux-en-Y pancreaticojejunostomy reconstruction is a safe and feasible procedure for the treatment of benign and borderline pancreatic neoplasms adjacent to the common pancreatic duct. This procedure can effectively mitigate the limitations of simple enucleation.